Engajamento discursivo: uma proposta de trabalho colaborativo - Oliveira, Silvia Regiane de Oliveira (2007)
This research aims at investigating how the discursive practices of a teacher, who is a participant of this study, provide student s engagement in discourse. It also aims at evaluating and reflecting upon these discursive actions, through reflective sessions performed between the teacher-participant and the coordinator-researcher, suggesting room for the reconstruction of these discursive actions. The present study was performed following the social historic perspective discussed by Vygotsky (1930-34) and it is also supported by the language dialogic comprehension expressed by Bakhtin (1929). In order to understand the concept of discursive engagement, the Parâmetros Curriculares Nacional de Língua Estrangeira were used as a reference, as well as texts about this subject published by Moita Lopes (2003-2004). This study was carried out in a public school located in the center of the city of Diadema and involved, apart from the researcher who holds the post of teaching coordinator of the school, an English teacher who used to teach at the same school. Two of this teacher s classes were recorded and two reflective sessions were performed with the participant of this study. Results suggest the possibility of developing some reflective work between the English teacher and the coordinator, carried out within the school, with the objective of developing a complete understanding of the discursive practices that promote student s participation. This kind of work may help the teacher to become aware of the influences of his/her actions on the quality of student s participation during the class